The social mobility of portuguese inmigrants in the United States at the turn of the nineteenth century - Benis Baganha, M. I.
tbls.
pp. 277-302
Keywords: Movilidad Social; Inmigrantes; Estados Unidos de America; Portugueses; Siglo XIX; Ocupaciones; Trabajadores Migratorios